Advances in Quantum Computing (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
The field of quantum information science has seen tremendous progress over the last several years, with advances in both hardware development and novel algorithms. This Special Issue has endeavored to capture some of the technical advances in this rapidly changing field.